2021
DOI: 10.1039/d1ra03983k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of ultra-high mechanical strength wear-resistant carbon fiber textiles with a PVA/PEG coating

Abstract: Polyvinyl alcohol (PVA) is an organic polymer that is non-toxic, harmless to the human body, and has good biocompatibility. Polyethylene glycol (PEG) is a polymer that has good lubricity and compatibility. As a new coating material, PVA/PEG has good mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…21 The biocompatibility of polyvinyl alcohol (PVA) and polyethylene glycol (PEG) in gel systems enable them to be used in a wide range of applications. 22 Chen et al 23 had prepared a PVA-HA/PAA compound hydrogel that has a favorable thermal stability and an excellent lubricating property by freeze-thawing and annealing methods. Gang et al 24 obtained composite hydrogels with nano-hydroxy apatite (HA) nanoparticles filled in polyvinyl alcohol hydrogel (PVA-H) and investigated its lubrication properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The biocompatibility of polyvinyl alcohol (PVA) and polyethylene glycol (PEG) in gel systems enable them to be used in a wide range of applications. 22 Chen et al 23 had prepared a PVA-HA/PAA compound hydrogel that has a favorable thermal stability and an excellent lubricating property by freeze-thawing and annealing methods. Gang et al 24 obtained composite hydrogels with nano-hydroxy apatite (HA) nanoparticles filled in polyvinyl alcohol hydrogel (PVA-H) and investigated its lubrication properties.…”
Section: Introductionmentioning
confidence: 99%
“…The special three‐dimensional structure of hydrogels gives them excellent water locking properties 21 . The biocompatibility of polyvinyl alcohol (PVA) and polyethylene glycol (PEG) in gel systems enable them to be used in a wide range of applications 22 . Chen et al 23 had prepared a PVA‐HA/PAA compound hydrogel that has a favorable thermal stability and an excellent lubricating property by freeze‐thawing and annealing methods.…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials, such as polymer‐polymer combinations, can produce hydrogels with better and desirable properties than those made from a single material, and these hydrogels can be intentionally modulated. Polyethylene glycol (PEG) is a biopolymer with a wide range of applications, having flexible COC chains, 23 being a component of artificial cartilage, as well as being well water soluble, nontoxic and immunologically inert, at the same time, providing good self‐lubricating properties as an important lubricant, and has been approved by the Food and Drug Administration for in vivo use as a biomacromolecular material 24 . Several investigations have increasingly shown that reactive oxygen species are a major cause of osteoarthritis, and Chen et al found that the addition of PEG showed significant improvement in scavenging reactive oxygen species as well as significant repair of articular cartilage structure 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Boric acid (BA) offers significant potential in the treatment of inflammatory conditions, effective in improving inflammation and promoting wound healing 24–26 . Poly(vinyl alcohol) (PVA) serves as a cross‐linking element to form hydrogels and is used by many researchers, which benefits from the beneficial biocompatibility and convenience of working with PVA 27 . Across systems, cross‐linking can be carried out with materials containing a large number of hydrogen atoms, and BA could be used to cross‐link hydrogels, which is a common study 28–30 .…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Poly(vinyl alcohol) (PVA) serves as a cross-linking element to form hydrogels and is used by many researchers, which benefits from the beneficial biocompatibility and convenience of working with PVA. 27 Across systems, cross-linking can be carried out with materials containing a large number of hydrogen atoms, and BA could be used to cross-link hydrogels, which is a common study. [28][29][30] Hyaluronic acid (HA) has been considered to play a role as a lubricant in joints, so the use of HA and its derivatives as a lubricant has been explored by many scholars.…”
Section: Introductionmentioning
confidence: 99%